Reverberations of Nazi violence in Germany and beyond: disturbing pasts - Bird, Stephanie; Fulbrook, Mary; Wagner, Julia; Wienand, Christiane (Bloomsbury Academic, 2016)
Introduction : disturbing the past, disturbed by the past / Stephanie Bird and Mary Fulbrook -- PART I. EMOTIONAL CONNECTIONS. Troubling issues : guilt and shame among persecutors and persecuted / Mary Fulbrook -- Shamed by Nazi crimes : the first step towards Germans' re-education or a catalyst for their wish to forget? / Ulrike Weckel -- Ashamed about the past : the case of Nazi collaborators and their families in postwar Dutch society / Ismee Tames -- Autobiography, moral witnessing, and the disturbing memory of Nazi euthanasia / Susanne Knittel -- PART II. DISTURBING NARRATIVES. Disturbing mending : on the imagined third generation of Holocaust survivors in Israeli literature of the second generation / Tsila Ratner -- Disturbing the past : the representation of the Waldheim Affair in Robert Schindel's Der Kalte / Katya Krylova -- The return of the Jew in Polish culture / Uilleam Blacker -- PART III. FASCINATION / PLEASURE. Don't mention the war / Julian Petley -- 'However sick a joke...' : on comedy, the representation of suffering, Rainer Werner Fassbinder's Melodrama and Volker Koepp's Melancholy / Stephanie Bird -- Disturbing Anselm Kiefer / Caitriona Leahy -- PART IV. BETTER FUTURES? : (DIS)PLACING IDENTITIES. German tourists in Europe and reminders of a disturbing past / Julia Wagner -- Reverberations of a disturbing past : reconciliation activities of young West Germans in the 1960s and 1970s / Christiane Wienand -- Disturbing pasts and better futures? : a comparison of recent approaches to the past among Bukovina Jews and Bukovina Germans / Gaelle Fisher -- How to cope with it? : the Steuben Society of America's politics of memory and the Holocaust / Julia Lange -- Afterword : hauntings and revisitings across generations / Lisa Appignanesi